Development of Marzano's Taxonomy-Based Evaluation Instrument to Determine the Reasoning Skill Profile on Straight Motion Material - SARI, CUPMA RIYA CIPTA; ., Tantri Mayasari; ., Mislan Sasono (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to produce a valid reasoning ability test instrument. This research is a research and development conducted using the four stages of the ADDIE model. Instrument validation is carried out by experts. The results of expert validation showed that overall the test instruments obtained good categories. The results of empirical validation show that five questions are valid and obtain a CVI of 1. Test instruments are carried out to measure reasoning ability. The measurement results show that the average value of students' problem solving skills is 18.18 with the highest value of 35 and the lowest 7.5 with a scale of 0-100